(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
Introduction: Rett Syndrome is a genetic disorder that limits a girl’s ability to use her upper extremities for daily activities, such as dressing and playing. One possible intervention to improve upper extremity function in this population is virtual reality, which can be used to increase activity demands during therapy sessions. Objectives: To determine the feasibility of using internet-based virtual reality intervention for Rett Syndrome (RTT-IVR), to decrease hand wringing/mouthing and increase hand and arm movements away from the midline by identifying attributes and limitations to the proposed intervention. Materials and Methods: Using FAAST Software and Microsoft Kinect sensor, RTT-IVR was trialed with 6 girls with RTT. Upper extremity movements were used to play free Internet games as means of increasing repetitions and purposeful arm movements. Data regarding attributes and limitations of the RTT-IVR intervention were collected via observation and post-session parent interviews. Results: Interviews and observation revealed successful game play when games were motivating, clearly established cause and effect, and matched level of cognitive ability of the participant. Limitations include technological glitches regarding Kinect sensor sensitivity and identifying appropriate games for each participant’s interests and abilities. Conclusion: Internet based virtual reality interventions for girls with RTT should be highly individualized to increase motivation and success of intervention.